2019
DOI: 10.1257/jep.33.1.185
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Justice: The Economics of Race, Place, and Pollution

Abstract: The grassroots movement that placed environmental justice issues on the national stage around 1980 was soon followed up by research documenting the correlation between pollution and race and poverty. This work has established inequitable exposure to nuisances as a stylized fact of social science. In this paper, we review the environmental justice literature, especially where it intersects with work by economists. First we consider the literature documenting evidence of disproportionate exposure. We particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
255
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 424 publications
(263 citation statements)
references
References 69 publications
8
255
0
Order By: Relevance
“…Traditionally, residential-based measurement is used for long-term (or life-time) exposure assessment [3]. It is typically assumed that people who live in the same neighborhood or geographic area, such as a census tract or zip code area, are exposed to a similar level of environmental influence [4,5]. The underlying presumption is that 2 of 19 people spend most of their time in their residential community, and thus, people who live in the same neighborhood may have the same level of exposure [6].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, residential-based measurement is used for long-term (or life-time) exposure assessment [3]. It is typically assumed that people who live in the same neighborhood or geographic area, such as a census tract or zip code area, are exposed to a similar level of environmental influence [4,5]. The underlying presumption is that 2 of 19 people spend most of their time in their residential community, and thus, people who live in the same neighborhood may have the same level of exposure [6].…”
Section: Introductionmentioning
confidence: 99%
“…Questions around facility siting are certainly important, and past studies have shown that race, ethnicity, and income are often correlated with the location of pollution sources [22,23]. The causal mechanism(s) behind these associations are still in dispute, but uncertainty about the social, economic, and political processes that lead to correlations between pollution and demographic attributes does not mean that their existence is unimportant [40]. Disparities, regardless of their cause are essential to document from an environmental justice perspective, and particularly so given that the category of pollution at issue are under-regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Suppose an area receives an exogenous increase of amenities, leading to increased housing costs. As the literature has already recognized, if the marginal bidder moving in during gentrification increases housing prices by more than poorer incumbents' willingness to pay for the increased amenity, incumbent renters could be made worse off (see, e.g., Banzhaf et al (2019)). Capitalization into tickets is likely to augment this effect.…”
Section: Resultsmentioning
confidence: 99%